Facilitators and barriers of empathetic behaviour in physiotherapy clinical practice : A qualitative focus group study - Savvoulidou, Konstantina; Papageorgiou, Alexia; Kolokotroni, Ourania; Kapreli, Panagiota; Tsokani, Aristi; Strimpakos, Nikolaos; Kapreli, Eleni (My University, 2024)
Empathy is an essential competence of a person-centered approach, and a recognisable ability for providing physiotherapy quality healthcare. Empathetic communication enhances the improvement of patient outcomes and their experience of treatment.
Keywords: Physiotherapy; Barriers; Empathy; Facilitators